Sources of individual variability: miRNAs that predispose to neuropathic pain identified using genome-wide sequencing - Bali, Kiran Kumar; Hackenberg, Michael; Lubin, Avigail; Kuner, Rohini; Devor, Marshall (Molecular pain, 2014)
We carried out a genome-wide study, using microRNA sequencing (miRNA-seq), aimed at identifying miRNAs in primary sensory neurons that are associated with neuropathic pain. Such scans usually yield long lists of transcripts regulated by nerve injury, but not necessarily related to pain. To overcome this we tried a novel search strategy: identification of transcripts regulated differentially by nerve injury in rat lines very similar except for a contrasting pain phenotype. Dorsal root ganglia (DRGs) L4 and 5 in the two lines were excised 3 days after spinal nerve ligation surgery (SNL) and small RNAs were extracted and sequenced.